Application of the Role Playing Model to Improve Student Learning Outcomes in Class IV Civics Learning at SD Negeri 69 Prabumulih: Penerapan Model Role Playing Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Pembelajaran PKn Kelas IV SD Negeri 69 Prabumulih - Lety Widya; Sutina (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2023)
The development of globalization has led to various ease of access in human life. These changes must be balanced with the readiness of human resource capabilities in dealing with them. Education is one way to equip Human Resources to face the times. To achieve these goals, education must be carried out with the right plans and designs through the learning process. This research seeks to improve student learning outcomes by applying the Role Playing learning model in class IV SD Negeri 69 Prabumulih in Civics subjects. The method used in this research is Classroom Action Research by carrying out learning through 3 cycles. In carrying out the learning process with the Classroom Action Research method, each cycle is evaluated and revised to find out the improvement of the learning process by applying the Role Playing model. The results obtained in this study are that it can be seen that in cycle 0 the behavior of student learning outcomes only reached 37% then in cycle 1 it increased to 63% and finally in cycle 2 it increased to 87%.